Drug reaction with eosinophilia and systemic symptoms/drug‐induced hypersensitivity syndrome: clinical features of 27 patients. (1st December 2015) - Avancini, J.; Maragno, L.; Santi, C. G.; Criado, P. R.
Summary: Background: Drug reaction with eosinophilia and systemic symptoms (DRESS) [also called drug‐induced hypersensitivity syndrome (DIHS)] includes severe reactions to drugs that need to be promptly recognized by physicians. Aim: To explore heterogeneity in the clinical presentation of DRESS/DIHS at a large academic hospital in Latin America, using the criteria defined by the European Registry of Severe Cutaneous Adverse Reactions (RegiSCAR) scoring system. Methods: A retrospective medical record review of 60 patients with diagnostic suspicion of DRESS/DIHS admitted to our hospital between July 2008 and April 2012 was performed, including demographic data, clinical features, laboratory findings and treatment. Results: Of the 60 patients, 27 fulfilled the criteria for DRESS/DIHS. Maculopapular exanthema (85.1%), fever (96.2%) and hepatic involvement (85.1%) were the most common features. Anticonvulsants were the most common causal drugs (77.7%); Phenytoin was the most common individual drug (44.4%), followed by carbamazepine (29.6%). All patients were treated initially with prednisone 1 mg/kg/day. Mortality rate was 4%. Conclusion: The major findings of this study (to our knowledge the largest collection of data on DRESS/DIHS in Latin America) include a positive statistical association between presence of atypical lymphocytes and higher levels of alanine aminotransferase ( P < 0.001) and reinforce the importance of anticonvulsants in the pathogenesis of this severe reaction.